Handling Religious and Community Diversity to Prevent Exclusive Religious Expression in the Multireligious Community of Mojokerto, East Java, Indonesia - Ridho, Akhsin; Hamdani, Moh. Salman (ADDIN, 2024)
This research addresses religious and community diversity to prevent exclusive religious expression in multireligious communities in Mojokerto, East Java, especially in Pohjejer Village. The village has a diverse social and religious background, with the majority of the population adhering to Islam, but there are also small groups of followers of other religions. The informants in this study consisted of 15 individuals selected purposively, including religious leaders, community leaders, members of religious organisations, and villagers involved in daily interfaith interactions. They were selected based on their central role in the social and religious dynamics of the village and their influence on the existing diversity. This study identifies factors that can trigger exclusive religious expression and provides insights into how interactions between religious communities can be managed to minimise potential conflicts. The findings show that an inclusive approach, interfaith education, and interfaith dialogue are key to maintaining harmony. The new contribution of this study is an emphasis on the importance of a more holistic understanding of social interaction in the context of Indonesia’s heterogeneous Islamic society, which can be an essential reference in Islamic studies related to the management of diversity in regions with similar characteristics.